Pengaruh latihan passing segitiga dan passing zig-zag untuk meningkatkan teknik passing pada ekstrakurikuler futsal SMA Negeri 2 Kendal - Endri Wiranto; Bertika Kusuma Prastiwi; Donny Anhar Fahmi (Journal of Physical Activity and Sports (JPAS), 2021)
The purpose of this research is for background abilities Passing Triangle and Passing Zig-Zag futsal extracurricular in SMA Negeri 2 Kendal. This research is an experimental study with a two group pretest-posttest method. The subjects of this study are 15 students of SMA Negeri 2 Kendal in the 15-17 age category, the sample taken is using purposive sampling technique, the instruments used in this study were wall passing, accuracy. The results of the research on the effect of the soccer resistance test training to improve the passing conditions of extracurricular students at SMA Negeri 2 Kendal during the football test had an increase as indicated by the value of Sig. (0.001) <? (0.05) which means that H0 is rejected. So there is a significant difference between the pretest and posttest in the practice of the football test in terms of increasing the accuracy of triangular passing and zigzag passing in the futsal ball extracurricular students of SMA Negeri 2 Kendal so that there is an effect of passing practice on increasing the accuracy of triangular passing and zigzag passing on extracurricular students of SMA Negeri 2 Kendal. The conclusions and suggestions from the results of this study can be used as a benchmark in compiling training programs. Keywords: Training Methods, triangle passing, zigzag passing and futsal